2014
DOI: 10.4103/0019-557x.146284
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between job satisfaction and performance of primary care physicians after the family physician reform of east Azerbaijan province in Northwest Iran

Abstract: The low scores of family physicians in performance and job satisfaction are obvious indications for more extensive research in identifying causes and finding mechanisms to improve the situation, especially in payment methods and work condition, in existing health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…As in other studies, females were found to be more satisfied than their male colleagues [19, 26, 27]. Male dominated societies, like India, dictate women to be in a more subservient position, may be the reason for this observation.…”
Section: Discussionsupporting
confidence: 74%
“…As in other studies, females were found to be more satisfied than their male colleagues [19, 26, 27]. Male dominated societies, like India, dictate women to be in a more subservient position, may be the reason for this observation.…”
Section: Discussionsupporting
confidence: 74%
“…Shortage of medicines is a source of annoyance and anger among patients which in turn can affect physicians' motivation. Evidence suggests that health workers perform better 45 when essential commodities and equipment are availed to them. This is because a completely equipped health facility and staff is necessary for comprehensive service delivery and patient care in healthcare setting.…”
Section: Discussionmentioning
confidence: 99%
“…The number of moderately satisfied, satisfied, and very satisfied physicians and dentists and sample sizes were pooled, resulting in an overall weighted percentage of 60% (95% CI 53%-67%), representing 14 113 physicians and dentists with substantial heterogeneity (I 2 = 98.21%; P < .001) ( Figure 4A). 46,47,52,53,55,58,59,81,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] Palmer-Morales et al, 40,41 2005 He et al, 87 Esquivel-Molina et al, 45 2007 Huri et al, 93 2016 Salem et al, 92 2018 Beltrán et al, 44 2004 Montenegro et al, 42 insufficient number of studies within each group. This concern was supported by a metaregression of dichotomous data, which suggested that job satisfaction levels did not differ significantly across countries with different income levels, but it was significantly higher among dermatologists (regression coefficient, 0.45; 95% CI, 0.13-0.89; P = .045) compared with other specialties (eAppendix 5 in the Supplement).…”
Section: Studies Were Published Between 1982 and 2018 Primarily Inmentioning
confidence: 99%